Trend of lipid and thyroid function tests in adults without overt thyroid diseases: A cohort from Tehran thyroid study - Ahi, Salma (PLoS One, 2019)
CONTEXT: While the role of overt hypothyroidism in lipid disorders is clear, the association between dyslipidemia and subclinical thyroid diseases remains unclarified. OBJECTIVE: To examine lipid trends based on thyroid function over a 10-year period. DESIGN: This is a prospective population based cohort study. SETTING: General community. PARTICIPANTS: 2383 euthyroid participants, as well as those with subclinical thyroid diseases, in all residents of district 13 of Tehran were examined. Subjects who were on levothyroxine, anti-hyperthyroid drugs, and glucocorticoids, those with a history of thyroid surgery or RAI and pregnant women were excluded. MAIN OUTCOME MEASURES: Lipid trends in Model 1 were adjusted for age and follow up duration, and in Model 2 gender-specific multivariate adjustments were performed for thyroid status, diabetes mellitus, smoking status, education, BMI, lipid lowering medications, age and follow up duration by using generalized estimating equations. RESULTS: In every four years of assessments, there were significant decreases in levels of all lipid parameters (all Ps <0.001) except for HDL-C, in which a decrescendo-crescendo trend was observed. The results did not change after adjusting for thyroid status, consumption of lipid lowering drugs during the follow-up period, or other variables. There were significant decreases in the prevalence of hypercholesterolemia and hypertriglyceridemia (all Ps <0.001) during the follow-up period. CONCLUSION: During a 10 year follow-up, decrescendo trends were observed in levels of total cholesterol, triglycerides, which were not be accounted for by the consumption of lipid lowering drugs and thyroid status.